2007
DOI: 10.1038/oby.2007.512
|View full text |Cite
|
Sign up to set email alerts
|

Short Sleep Duration is Associated with Reduced Leptin Levels and Increased Adiposity: Results from the Québec Family Study

Abstract: CHAPUT, JEAN-PHILIPPE, JEAN-PIERRE DESPRÉ S, CLAUDE BOUCHARD, AND ANGELO TREMBLAY. Short sleep duration is associated with reduced leptin levels and increased adiposity: results from the Québec Family Study. Obesity. 2007;15:253-261. Objective: To explore cross-sectional associations between short sleep duration and variations in body fat indices and leptin levels during adulthood in a sample of men and women involved in the Québec Family Study. Research Methods and Procedures: Anthropometric measurements, pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
302
4
23

Year Published

2009
2009
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 447 publications
(350 citation statements)
references
References 27 publications
21
302
4
23
Order By: Relevance
“…The change in the ghrelin/leptin ratio between the two experimental conditions was significantly and positively correlated with changes in hunger ratings, suggesting that sleep restriction-induced alterations in these hormones may, in part, be driving observed increases in hunger ratings. These results are consistent with findings from two population-based studies that have also reported associations between short sleep duration, leptin, and ghrelin levels consistent with an up-regulation of appetite (71,72). Moreover, these associations were independent of BMI and other possible confounding factors.…”
Section: Methodology and Findings Of Previous Laboratory Studiessupporting
confidence: 82%
“…The change in the ghrelin/leptin ratio between the two experimental conditions was significantly and positively correlated with changes in hunger ratings, suggesting that sleep restriction-induced alterations in these hormones may, in part, be driving observed increases in hunger ratings. These results are consistent with findings from two population-based studies that have also reported associations between short sleep duration, leptin, and ghrelin levels consistent with an up-regulation of appetite (71,72). Moreover, these associations were independent of BMI and other possible confounding factors.…”
Section: Methodology and Findings Of Previous Laboratory Studiessupporting
confidence: 82%
“…Among obese women, the metabolically healthy reported 0.6 hours longer sleep duration than at risk obese. Although shorter sleep duration has often been associated with obesity in crosssectional and prospective studies, 33,34 this is the first report of an association with the at risk obesity phenotype. It is hypothesized that shorter sleep duration and obesity may be linked through neuroendocrine changes that influence appetite and favor a positive caloric balance, 34 or through behaviors often correlated with short sleep duration, such as television viewing time and consumption of high energy foods.…”
Section: Discussionmentioning
confidence: 98%
“…Outra questão ainda sem conseso na literatura é a definição de privação de sono. As definições de duração de sono normal variam entre 6 a 9 horas por dia [35], porém distúrbios metabólicos e ganho de peso podem ser observados em indivíduos que dormem menos do que 6 horas por dia [42][43][44].…”
Section: Discussionunclassified